SHARING SESSION SUASANA AKADEMIK DI LUAR NEGERI BAGI MAHASISWA TEKNOLOGI INFORMASI UNTUK MENINGKATKAN MOTIVASI BERINOVASI - Wiga Maulana Baihaqi; Atika Nurlaeli; Rizky Adhytia; Muhammad Luqman (LPPM Universitas Al Muslim, 2023)
The Information Technology Study Program, Faculty of Computer Science, Amikom University, Purwokerto, has grown in terms of the number of students, but requires accreditation by the Ministry of Education and Culture. Active involvement of students in various activities is a key factor in achieving good accreditation results. However, some students were not involved in extracurricular activities, which limits their knowledge, skills, social networks, and interpersonal skills. Lack of motivation, interest, and opportunities to innovate were identified problems. A program was proposed to address two problems facing Purwokerto University Amikom Information Technology students: lack of motivation to seek additional experience and engage in innovation, and underutilization of PkM activities and study center programs. The proposed solution was in the form of a sharing session about studying abroad, where students will learn about the IT student atmosphere at Amikom Purwokerto and gain motivation to innovate. This program involved a partnership with the Malaysian Technical University Melaka, where Assoc. Prof. Dr. Ahmad Naim Che Pee as resource person and guide. The results of the activities carried out showed that student motivation increased to be more innovative, for lecturers to make students aware that they would involve students in research activities and community service, as well as for study centers to manage programs that inspired students to develop innovation.